Lending structure and bank insolvency risk : a comparative study between Islamic and conventional Bank. - A. Rahman, Aisyah; Ibrahim, Mansor; Mydin Meera, Ahamad Kameel (World Business Institute, 2009)
This study investigates the impact of lending structure on the insolvency risk exposure. A comparative analysis between the insolvency risk behavior between the Islamic and conventional banks is made. Our findings show that real estate lending is positively related to the conventional banks’ risk, but inversely related to the Islamic banks’ risk exposure. Thus, the policy makers as well as the banks should react accordingly in the decision making process.